Pathological Mechanisms Involved in HIV-Associated Lymphomagenesis: Novel Targeted Therapeutic Approaches - Mihaela Straista; Francesca Caccuri; Nicoleta Arnaut; Arnaldo Caruso; Mark Slevin (Cells)
The intricate interplay of direct and indirect mechanisms relating to immune dysfunction, chronic inflammation, and viral proteins represents a key factor of lymphomagenesis in HIV-infected patients. Indirect mechanisms based on cytokine dysregulation, HIV-induced immune dysfunction, and co-infections with oncogenic viruses induce chronic B-cell activation and generation of a prone environment for malignant transformation and tumor growth. Direct mechanisms arise from oncogenic influences of p17, Tat, and Nef HIV proteins, which generate genomic instability, alteration of cellular signaling, and activation of oncogenic pathways. Vp17’s implication in lymphomagenesis and angiogenesis, ensured by activation of PAR1/EGFR/PI3K/Akt and MEK/ERK1/2 pathways, emphasizes the critical need for developing therapeutic strategies that target their signaling mechanisms. This review shows an insight into the pathological mechanisms involved in lymphomagenesis in HIV-infected individuals, focusing on finding novel therapeutic approaches directed at immune rehabilitation and oncogenic signaling pathways.